Sequoia affects Drosophila central nervous system development by regulating axonal extension and guidance - Noor Al-Hajri; Raquel Mendez-Castro; Mar Alujas; Sofia J. Araújo; Guy Tear (PLoS ONE, 2026)
The development of the Drosophila melanogaster central nervous system (CNS) requires both determination of neuronal cell types and the subsequent establishment of neural connectivity. Numerous studies have identified genes and molecules required for both these processes. Once neurons have differentiated, they are guided to their targets by attractive and repulsive forces and an increasing number of molecules that provide these functions have been identified. However, little is known on how molecules involved in neuronal differentiation might affect subsequent steps of axonal development such as axonal morphogenesis. The sequoia ( seq ) mutant was identified in a Drosophila genetic screen for defects in dendrite elaboration. Sequoia is a pan-neural nuclear protein containing two putative zinc-fingers homologous to the DNA binding domain of Tramtrack. Mutations in seq have been reported to affect the cell fate decision of external sensory organ neurons and to effect axon and dendrite morphology. Previous reports have focused mainly on the effects this mutation causes in dendritic morphogenesis in the peripheral nervous system (PNS). Amongst mutants isolated from a previous mutagenesis screen, we have identified three new alleles of sequoia , GA168, C022 and C3101 and identify the molecular lesions in two previously identified alleles, Z1241 and H156. Analysis of these five alleles has revealed that seq mutations lead to several defects in nervous system development. seq mutants show defects in the spatial organization of their CNS from early developmental stages and have abnormal cell morphology, both at early and late stages of embryonic development. Mutations in seq affect motor axon outgrowth and general CNS and PNS development. The reported seq mutations reveal an important link between neuronal differentiation and axonal outgrowth and guidance and shed light on the importance of different Seq domains.